La carencia afectiva y su relación con los trastornos psicológicos en los niños de primero de básica de la escuela internacional “San Ignacio de Loyola riobamba período enero – marzo 2012. - Guijarro Orozco, Carolina Alexandra (2012)
The present investigating work has like main objective to determine how the affective scarcity influences development and the boys and girls's behavior, through an investigating guide; the same that is based on the systemic familiar therapy using the inductive method, fact-finding guy. It was used for the collection of data: Opinion polls and interviews to the family men, clinical evaluation and psychometric applied to the School's children San Ignacio of Loyola of Riobamba's City, period January - March 2012. Research findings suggest than 83 % of the children ace you presented, 1 own characteristic of the affective scarcity; Situation that you show in great magnitude the influence of the affectivity enough, since the children's inadequate behavior ace (challenging, enuresis, provokers) at the home and the school is sincere.